Immobilized Saccharomyces cerevisiae viable cells for electrochemical biosensing of Cu(II) - Ehtisham Wahid; Ohiemi Benjamin Ocheja; Sunday Olakunle Oguntomi; Run Pan; Matteo Grattieri; Nicoletta Guaragnella; Cataldo Guaragnella; Enrico Marsili (Scientific Reports)
Abstract Electrodes functionalised with weak electroactive microorganisms offer a viable alternative to conventional chemical sensors for detecting priority pollutants in bioremediation processes. Biofilm-based biosensors have been proposed for this purpose. However, biofilm formation and maturation require 24–48 h, and the microstructure and coverage of the electrode surface cannot be controlled, leading to poorly reproducible signal and sensitivity. Alternatively, semiconductive biocompatible coatings can be used for viable cell immobilization, achieving reproducible coverage and resulting in a stable biosensor response. In this work, we use a polydopamine (PDA)-based coating to immobilize Saccharomyces cerevisiae yeast viable cells on carbon screen printed electrodes (SPE) for Cu(II) detection, with potassium ferricyanide (K3[Fe (CN)6]) as a redox mediator. Under these conditions, the current output correlates with Cu (II) concentration, reaching a limit of detection of 2.2 µM, as calculated from the chronoamperometric response. The bioelectrochemical results are supported by standard viability assays, microscopy, and electrochemical impedance spectroscopy. The PDA coatings can be functionalised with different mutant strains, thus expanding the toolbox for biosensor design in bioremediation.